The Impact of Infrastructure on Employee Performance: Organizational Culture as a Mediating Variable (A Field Study in the Jordanian Income and Sales Tax Department) - Al-Rousan, Mahmoud Ali; Ababneh, Ayat Muhammad Nabil Wahib (Ekonomika, 2025)
This study aims to identify the impact of digital infrastructure in its dimensions (hardware components, software, communication networks, databases, human skills) on the performance of employees in its combined dimensions (work speed, work quality, and knowledge of work requirements) with the presence of organizational culture as an intervening variable in the Jordanian Income and Sales Tax Department. The study community may have been employees in the Jordanian Income and Sales Tax Department, and the research community was represented by a sample of (220) individuals. The simple random sample was adopted, and, in order to achieve the objectives of the study, the descriptive analytical approach was relied upon through a questionnaire that was distributed to the sample individuals and analyzed afterwards. The number of the distributed questionnaires was (250) questionnaires, of which, (220) questionnaires were deemed to be suitable for analysis, representing (48%) of the total community. The data were analyzed, and the hypotheses were tested using the (SPSS) software and adopting simple linear regression and hierarchical multiple regression. The study has yielded several results, the most important of which is the existence of a statistically significant effect at a significance level (a≤0.05) of the digital infrastructure in its dimensions on the performance of employees in its dimensions combined; it has also been established that there is a statistically significant effect of the digital infrastructure on the performance of employees with the presence of the organizational culture as an intervening variable. Several recommendations have been presented based on the results of the analysis, the most important of which are: (1) enhancing the use of advanced technological means, (2) providing opportunities for training and continuing education, and (3) providing a positive work environment.